The treatment of "shooting" pain. Issue 653 (March 1980) - Swerdlow, M.
Abstract : Anticonvulsant drugs were given to 70 patients suffering from lancinating pains of various clinical aetiologies. Serum drug estimations were used to ensure that an effective dose level was achieved. In about 66% of the cases, treatment produced some diminution in the intensity and/or frequency of the "flashes" of pain. The neurophysiological and pharmacological rationales are briefly explained. It is concluded that this use of anticonvulsant agents merits further study.